2014
DOI: 10.1007/s11894-014-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined Multichannel Intraluminal Impedance-pH (MII-pH): Multicenter Report of Normal Values from 117 Children

Abstract: Although combined multichannel intraluminal impedance/esophageal pH monitoring (MII-pH) has replaced prolonged pH monitoring alone for assessing gastroesophageal reflux (GER) in the pediatric population, it does so in the absence of reference values for non-acid GER (NAGER). The purpose of this study was to identify a normal range of NAGER impedance values for infants and children. We evaluated EPM/MII tracings for patients referred for GER assessment to Nationwide Children's Hospital (Columbus, OH), Inova Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 16 publications
10
57
1
4
Order By: Relevance
“…The median number of reflux episodes in a 24-hour period was 71 (100, 95th percentile), the median total acid exposure was 5.59% (20%, 95th percentile)(3). More recently, Mousa et al (22) reported reference values for impedance data from 117 infants and children. They found similar results of total reflux episodes for 24 hours during infancy (median 54, 95th percentile 93).…”
Section: Discussionmentioning
confidence: 99%
“…The median number of reflux episodes in a 24-hour period was 71 (100, 95th percentile), the median total acid exposure was 5.59% (20%, 95th percentile)(3). More recently, Mousa et al (22) reported reference values for impedance data from 117 infants and children. They found similar results of total reflux episodes for 24 hours during infancy (median 54, 95th percentile 93).…”
Section: Discussionmentioning
confidence: 99%
“…Reflux episodes may be higher in infants than in children [6,7], but correlation with gestational age has not been assessed. It may be that the apparent association of apnoea and GOR episodes can be explained by the fact that they both have an inverse relationship with maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Oesophageal acid exposure time of >7% is abnormal while values between 3% and 7% are indeterminate 1. A report of normal values in a cohort of normal infants and children by Mousa et al 19 produced similar results (table 3). …”
Section: Discussionmentioning
confidence: 70%